Canada and the cost of World War II : the international operations of Canada's Department of Finance, 1939-1947 - Bryce, Robert B. (Robert Broughton), 1910- (Carleton library series, 2005)
"Canada's Department of Finance during World War II was surprisingly small - a tightly knit coterie of only a few hundred civil servants who managed the country's finances through the dark years of the war and the difficult period of reconstruction that followed. At the centre of this group was an inner circle - a handful of men - whom the deputy minister, Clifford Clark, relied on to shape public policy. This inner circle included Clark, W.A. Mackintosh, A.F.W. Plumptre, a young Mitchell Sharpe, and a young graduate of Cambridge and student of John Maynard Keynes, Robert Bryce, who came to the department in the late 1930s and quickly became a confidant of the deputy minister. During this period little public policy passed through Ottawa that did not bear the stamp of these men." "Reconstructed from archival sources and memory, Canada and the Cost of World War II is Bryce's definitive work on the department during these crucial years as well as an intimate portrait of the civil servants whose war for their country was waged with ledger sheets."--Jacket